ANALISIS SISTEM PENGELOLAAN PENDIDIKAN DALAM PERSPEKTIF KEPEMIMPINAN DI SEKOLAH - Lirra Zanni; Salam; Siti Inganah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the education management system from the perspective of school leadership in the implementation of the Educational Unit Operational Curriculum (KOSP). A qualitative descriptive approach was used, with data collection techniques including interviews, observation, and documentation. Subjects included the principal, teachers, and educational staff at Muhammadiyah 1 Elementary School, Bontang. The results indicate that the education management system has been systematically developed through the KOSP document, which includes the vision, mission, objectives, and learning programs. However, the effectiveness of implementation is greatly influenced by the principal's leadership capacity. Participatory and transformational leadership have been shown to contribute to improving the quality of learning, school culture, and teacher performance.